2010
DOI: 10.1259/bjr/33431002
|View full text |Cite
|
Sign up to set email alerts
|

An atypical cause of trigeminal neuralgia and panhypopituitarism

Abstract: A 63-year-old man presented to the hospital accident and emergency department with an episode of syncope. He also gave a history describing several weeks of leftsided facial pain, which was initially thought to be secondary to a tooth abscess. On systemic enquiry the patient also reported having intermittent episodes of night sweats and mild anorexia, but he was otherwise well. Physical examination revealed the patient to have significant postural hypotension, allodynia affecting all three divisions of the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Nearly three-fourth (76.5%) of the dentists correctly reported brain tumor as one of the etiologic factors of trigeminal neuralgia. Some studies have reported trigeminal neuralgia as one of the manifestations of intracranial tumors such as central nervous system lymphoma [ 33 ], meningioma [ 34 ], cerebellopontine angle tumors such as cholesteatoma [ 35 ], and epidermoid tumor [ 36 ]. Therefore, dentists should consider brain tumors as differential diagnoses when facing patients with trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly three-fourth (76.5%) of the dentists correctly reported brain tumor as one of the etiologic factors of trigeminal neuralgia. Some studies have reported trigeminal neuralgia as one of the manifestations of intracranial tumors such as central nervous system lymphoma [ 33 ], meningioma [ 34 ], cerebellopontine angle tumors such as cholesteatoma [ 35 ], and epidermoid tumor [ 36 ]. Therefore, dentists should consider brain tumors as differential diagnoses when facing patients with trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, uncommon in this case series. The presence of dural enhancement has also been described as a distinguishing feature of pituitary lymphoma, which is usually absent in pituitary adenomas (5) (8) . It is difficult to distinguish pituitary metastases due to lymphoma from other malignant tumours radiologically unless a pituitary biopsy is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Pese a que el LPSNC presenta sensibilidad a la quimio y radioterapia (13) , el pronóstico sigue siendo poco favorable con tiempos de supervivencia que oscilan entre 15 y 45 meses en aquellos pacientes que reciben tratamiento (11) , esto puede deberse tanto a la agresividad que per se posee esta neoplasia (7,12) , como al diagnóstico tardío (2) . La evolución de nuestra paciente fue poco favorable dada la presencia de recaída tumoral temprana posterior a dos ciclos de quimioterapia y trasplante autólogo de médula ósea, que determinó el inicio de terapia de rescate con metotrexate y citarabina en altas dosis, así como la utilización de radioterapia externa holoencefálica.…”
Section: Figura 2 Reporte Histopatológico De Biopsia Cerebral Región Núcleo Basal Izquierdaunclassified